THE ROLE OF YAYASAN BADAN WAKAF SULTAN AGUNG (YBWSA) IN WAQF ASSETS MANAGEMENT IN SEMARANG IN 1950-1980 - Mulyati, Mulyati (Walasuji : Jurnal Sejarah dan Budaya, 2020)
This research aims to examine the origins and developments of charitable business for one of the biggest waqf agencies in Indonesia, namely Yayasan Badan Wakaf Sultan Agung (YBWSA). Waqf in Indonesia is not something new. Research on waqf in Indonesia generally issues on regulation and accounting aspects, the historical aspect is rarely issued. In relation to socio-economic problems, the most visible impact of the establishment of YBWSA is to help the government and contribute to improve the people's welfare and their living standard. The result of this research shows that YBWSA is one of the biggest waqf foundations in Indonesia which arose due to the concerns of Islamic leaders in Semarang regarding the education system implemented during the Dutch East Indies government. The waqf received by YBWSA is used for development of educational purposes and it has now expanded to health services